(De)criminalisation of psychedelics in the Czech Republic-Where are we heading in drug policy and legislation? - Dleštíková, Tereza (The International journal on drug policy, 2022)
The article deals with the issue of decriminalization of drugs, in all relevant contexts, both in terms of criminal policy and legislation, as well as law enforcement, with focus on the Czech Republic. The article proceeds deductively from the general to the specific. First, it discusses the role of law in society and its legitimacy, with focus on legitimate criminal sanctions, which are discussed in the context of the principle of subsidiarity of criminal repression and the principle of opportunity (discretionary prosecution). After these general considerations, the article turns to the issue of drugs and discusses both drug policy and legislation, arguing that the general considerations are in favor of decriminalization tendencies in this area. In the final part, the article focuses on psychedelics, emphasizing a fundamental discrepancy between their factual and legal status and then considering ways of changing the perspective. At this point, the article outlines the importance of decriminalization of psychedelics for therapeutic use, which basically consist of rescheduling of these drugs. The aim of such decriminalization is to make psychedelic-assisted therapy legally available. The article concludes that this is the direction that criminal policy and law in the Czech Republic should take.
Keywords: Hallucinogens; prosazení zákonů; Law Enforcement; Česká republika; Drug policy; lidé; veřejná politika; Law and society; halucinogeny; Czech Republic; Public Policy; Rescheduling; zločinci; Decriminalization; zákonodárství lékové; Humans; Criminals; Legislation, Drug; Psychedelics